Reflection of internal waves by sand ripples - Samiran Mandal; Uma Basu (International Journal of Mathematics and Mathematical Sciences)
An investigation is made to study the diffraction of a train of time harmonic progressive waves propagating along the surface of separation of two superposed fluids which are laterally unbounded, the upper fluid being extended infinitely upwards, the lower fluid being of finite depth with sand ripples at the bottom. The first order correction to the velocity potential for the problem of diffraction of interface waves in the presence of bottom deformation is obtained by integral transform technique after introduction of a linear frictional term in the kinematic boundary condition at the surface of separation following Lamb (1932), and the reflection and transmission coefficients are estimated for a patch of sand ripples.